The Pilgrimage - Paulo Coelho (HarperCollins India, 1997)
On a legendary road across Spain, travelled by pilgrims of San Tiago, we find Paulo Coelho on a contemporary quest for ancient wisdom. This journey becomes a truly initiatory experience, and Paulo is transformed forever as he learns to understand the nature of truth through the simplicity of life. The Piligrimage has a very important place in the work of Paulo Coelho, not just because it is the first of his major books, after which came the Alchemist, but because of the complete way in which it expresses the humanity of Paulo's philosophy and the depth of his search.